Sharp-switching band-modulation back-gated devices in advanced FDSOI technology. (February 2017) - El Dirani, Hassan; Fonteneau, Pascal; Solaro, Yohann; Legrand, Charles-Alex; Marin-Cudraz, David; Ferrari, Philippe; Cristoloveanu, Sorin
Abstract: A band-modulation device with a free top surface, named Z 3 -FET (Zero front-gate, Zero swing slope and Zero impact ionization) and fabricated in the most advanced Fully Depleted Silicon-On-Insulator technology, is demonstrated experimentally. Since the device has no front gate, the operation mechanism is controlled by two adjacent heavily doped buried ground planes acting as back-gates. Characteristics such as sharp quasi-vertical switching, low leakage, and tunable trigger voltage are measured and discussed. We explore several variants (thin and thick silicon or SiGe body) and show promising results in terms of high current, switching performance and ESD capability with relatively low back-gate and drain bias operation.